Food colloid science and the art of computer simulation - Barker, Gary C.; Grimson, Malcolm J. (Food hydrocolloids, 1989)
This article contains an elementary review of modern computer simulation methods and an introduction to their applications to problems in the structure and dynamics of food colloids. The review includes sections on Monte Carlo methods, dynamic algorithms and packing simulations. In each case the object is to explain the basic principles of the method and its relation to the underlying physics, and to clarify the computational process without presenting any technical details of numerical methods or of particular implementations which can be found elsewhere. The computational schemes are illustrated by recent examples of their applications to systems which include models of emulsions, foams, aggregates and sediments. Within the area of colloid science computer simulations provide an invaluable complement to analytical theories and experiments. Possible advances and extensions of the computational approach are indicated in the discussion and the review is completed by a small glossary of computational terms which may prove useful to the non-specialist.